Production of Prodiginines Is Part of a Programmed Cell Death Process in Streptomyces coelicolor - Tenconi, Elodie; Traxler, Matthew F.; Hoebreck, Charline; van Wezel, Gilles P.; Rigali, Sébastien (Frontiers in Microbiology, 2018)
Actinobacteria are prolific producers of antitumor antibiotics with antiproliferative activity, but why these bacteria synthetize metabolites with this bioactivity has so far remained a mystery. In this work we raised the hypothesis that under certain circumstances, production of antiproliferative agents could be part of a genetically programmed death of the producing organism. While programmed cell death (PCD) has been well documented when Streptomyces species switch from vegetative (nutrition) to aerial (reproduction) growth, lethal determinants are yet to be discovered. Using DNA-damaging prodiginines of Streptomyces coelicolor as model system, we revealed that, under certain conditions, their biosynthesis is always triggered in the dying zone of the mycelial network prior to morphological differentiation, right after an initial round of cell death. The programmed massive death round of the vegetative mycelium is absent in a prodiginine nonproducer (ΔredD strain), and mutant complementation restored both prodiginine production and cell death. The redD null mutant of S. coelicolor also showed increased DNA, RNA, and proteins synthesis when most of the mycelium of the wild-type strain was dead when prodiginines accumulated. Moreover, addition of the prodiginine synthesis inhibitors also resulted in enhanced accumulation of viable filaments. Overall, our data enable us to propose a model where the time-space production of prodiginines is programmed to be triggered by the perception of dead cells, and their biosynthesis further amplifies the PCD process. As prodiginine production coincides with the moment S. coelicolor undergoes morphogenesis, the production of these lethal compounds might be used to eradicate the obsolete part of the population in order to provide nutrients for development of the survivors. Hence, next to weapons in competition between organisms or signals in inter- and intra-species communications, we propose a third role for antibiotics (in the literal meaning of the word ‘against life’) i.e., elements involved in self-toxicity in order to control cell proliferation, and/or for PCD associated with developmental processes.